2011
DOI: 10.1038/bjc.2011.545
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to explore circulating tumour cells in pancreatic cancer as a novel biomarker

Abstract: Background:Obtaining tissue for pancreatic carcinoma diagnosis and biomarker assessment to aid drug development is challenging. Circulating tumour cells (CTCs) may represent a potential biomarker to address these unmet needs. We compared prospectively the utility of two platforms for CTC enumeration and characterisation in pancreatic cancer patients in a pilot exploratory study.Patients and methods:Blood samples were obtained prospectively from 54 consenting patients and analysed by CellSearch and isolation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
220
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(232 citation statements)
references
References 42 publications
(59 reference statements)
9
220
2
1
Order By: Relevance
“…We used procedures of this platform and CTCs definition criteria according to previous detailed reports. 33 ISET membrane spots were cut and submitted to immunocytochemistry with anti-CD45 antibody (1:100; clone 2B11 C PD7/26, Dako TM ), a surface leukocyte marker, in order to differentiate them from the CTCs. For CTCs counting, 8 spots from the ISET filter were used (corresponding to 8 mL of blood), after staining with hematoxylin and eosin.…”
Section: Patientsmentioning
confidence: 99%
“…We used procedures of this platform and CTCs definition criteria according to previous detailed reports. 33 ISET membrane spots were cut and submitted to immunocytochemistry with anti-CD45 antibody (1:100; clone 2B11 C PD7/26, Dako TM ), a surface leukocyte marker, in order to differentiate them from the CTCs. For CTCs counting, 8 spots from the ISET filter were used (corresponding to 8 mL of blood), after staining with hematoxylin and eosin.…”
Section: Patientsmentioning
confidence: 99%
“…In one study based on the ISET method, CTCs were found in 18 of 29 patients (62.0%) with primary invasive melanoma and in five out of eight patients (62.5%) with metastatic melanoma (De Giorgi et al, 2010). Khoja et al (2012) compared CellSearch and ISET in terms of CTC detection in 54 patients with pancreatic cancer, and found that ISET detects a higher number of CTCs than the CellSearch System. Polymerase chain reaction (PCR)‐based methods are also commonly used; CTCs were detected in 33.8–84% of patients by using Nested PCR with CK20 mRNA as a CTC marker in different studies (Soeth et al, 2005; Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although the liver is the most common target of pancreatic cancer with the exception of the lymph nodes, effective methods for prediction and treatment of liver metastasis remain unestablished (7,8). Identification of prognostic markers of metastasis would be useful for the management of post-operative patients with pancreatic cancer (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%